Clostridium Botulinum and Foodborne Illness - Pesaresi Penner, Karen; Blakeslee, Karen (My University, 1995)
This publication describes C. botulinum and how to prevent it.
MF2171_1995_11
Keywords: MF2171; Health and Safety; MF